From the Bench to Bedside: Biological and Methodology Considerations for the Future of Companion Diagnostics in Nonsmall Cell Lung Cancer - Dimou, Anastasios (SAGE-Hindawi Access to Research, 2011)
Companion diagnostics are an emerging and exciting field in the care of oncology patients. These tests accompany standard diagnostic investigations in cancer patients and function as an aid in treatment decision making. A great number of new compounds are under clinical and laboratory testing in nonsmall cell lung cancer (NSCLC). As the variety of therapeutic options expands in the various settings of the disease, it becomes apparent that specific and sensitive molecular tests are necessary to define the subsets of patients who are going to derive clinical benefit. Testing for epidermal growth factor receptor (EGFR) somatic mutations for the appropriate administration of tyrosine kinase inhibitors is just the beginning. Anaplastic lymphoma kinase (ALK) fusion protein detection and molecular histology classification are promising candidate predictors for clinical benefit from crizotinib and pemetrexed, respectively. This paper summarizes such diagnostics and discusses unanswered questions concerning underlying biology and standardization issues.